Comportamento da composição corporal, contagem elucocitária e adipocinas de adolescentes obesos treinados e não treinados - Antunes, Barbara de Moura Mello [UNESP] (2013)
Objective: To analyze the effects of 20 weeks of concurrent training in body composition, concentrations of pro and anti-inflammatory adipokines and leukocyte of obese adolescents of both genders. Methods: The sample consisted of 22 adolescents, with a mean age of 12.7 years (SD = 1.68), classified as obese. Assessment of body composition was performed by means of anthropometry, DEXA and ultrasound, and to assess the concentration of leukocytes and adipokines made biochemical analyzes. The sample was divided into control group and training group. The intervention group was training through the concurrent training, comprising 50 % of the time aerobic exercise and 50 % of the time resistance exercise, during 1 hour/session. Statistical analyzes (descriptive analysis, paired Student t test, Anova factorial, Pearson correlation and linear regression) were performed using SPSS, version 17.0, and statistical significance set at p<0,05. Results: After intervention there were significant changes in body composition, however not observed changes in blood variables. There is correlation between sex and percentage of total and trunk fat and total and android region of lean mass, moreover, the training has added sex ratio with total body mass, total fat mass, android region tissues (lean mass, fat mass and tissue), intra-abdominal fat and monocytes. The concentration of TNF-α correlated with age, weight, fat mass, lean mass and subcutaneous fat and to apply the body composition variables in a linear regression all variables maintained interaction with TNF-α, however, when adjusted for age, weight and sex, only fat mass and lean mass. Regarding the leukocyte count only IL-6 was correlated with cells and remained on the regression model. Conclusion: Obese adolescents submitted to concurrent training presented significant changes in body composition, however, do not change the leukocyte counts. Moreover, body composition variables, particularly fat...